Motivations and experiences of students in online Chinese as a foreign language learning: challenges and potential solutions - Xu, Yusi (My University, 2026)
The rapid expansion of online Chinese as a Foreign Language (CFL) learning presents unique motivational challenges. Grounded in Dörnyei’s L2 Motivational Self System, this study investigates how learners actively navigate, negotiate, and reshape digital environments to sustain their engagement. Adopting a qualitative, quasi-ethnographic case study design, the research examined the experiences of adult CFL learners in an online performance-based course. Data collected through semi-structured interviews, reflective journals, and forum analysis provided deep insight into the participants’ evolving strategies over eight weeks. The findings reveal that the online environment is a site of conflict between divergent learner “mental models.” A fundamental clash exists between utilitarian learners, who view the community as a “functional help desk” for efficiency, and relational learners, who seek a “supportive home” for identity validation. This dichotomy profoundly influenced how participants perceived peer feedback, defined “noise,” and interpreted silence. Crucially, learners exercised significant agency, employing strategies ranging from avoidance to active community creation to align the flawed digital environment with their needs. Based on these findings, the study proposes a new typology of online learners and challenges monolithic instructional design. The dissertation concludes by advocating for flexible, modular design philosophies to accommodate the diverse motivational profiles of modern digital learners.
Keywords: Online language learning; Chinese as a foreign language; L2 motivation; Learner agency; Computer-assisted language learning; Online learning communities